Phosphorylation of Drosophila CENP-A on serine 20 regulates protein turn-over and centromere-specific loading. Issue 20 (19th September 2019) - Huang, Anming; Kremser, Leopold; Schuler, Fabian; Wilflingseder, Doris; Lindner, Herbert; Geley, Stephan; Lusser, Alexandra
Abstract: Centromeres are specialized chromosomal regions epigenetically defined by the presence of the histone H3 variant CENP-A. CENP-A is required for kinetochore formation which is essential for chromosome segregation during mitosis. Spatial restriction of CENP-A to the centromere is tightly controlled. Its overexpression results in ectopic incorporation and the formation of potentially deleterious neocentromeres in yeast, flies and in various human cancers. While the contribution of posttranslational modifications of CENP-A to these processes has been studied in yeast and mammals to some extent, very little is known about Drosophila melanogaster . Here, we show that CENP-A is phosphorylated at serine 20 (S20) by casein kinase II and that in mitotic cells, the phosphorylated form is enriched on chromatin. Importantly, our results reveal that S20 phosphorylation regulates the turn-over of prenucleosomal CENP-A by the SCF Ppa -proteasome pathway and that phosphorylation promotes removal of CENP-A from ectopic but not from centromeric sites in chromatin. We provide multiple lines of evidence for a crucial role of S20 phosphorylation in controlling restricted incorporation of CENP-A into centromeric chromatin in flies. Modulation of the phosphorylation state of S20 may provide the cells with a means to fine-tune CENP-A levels in order to prevent deleterious loading to extra-centromeric sites.